Enforcement and Public Corruption: Evidence from US States - James E. Alt; David Dreyer Lassen (University of Copenhagen, Economic Policy Research Unit (EPRU), 2010)
We use high-quality panel data on corruption convictions, new panels of assistant U.S. attorneys and relative public sector wages, and careful attention to the consequences of modeling endogeneity to estimate the impact of prosecutorial resources on criminal convictions of those who undertake corrupt acts. Consistent with system capacity arguments, we find that greater prosecutor resources result in more convictions for corruption, other things equal. We find more limited, recent evidence for the deterrent effect of increased prosecutions. We control for and confirm in a panel context the effects of many previously identified correlates and causes of corruption. By explicitly determining the allocation of prosecutorial resources endogenously from past corruption convictions and political considerations, we show that this specification leads to larger estimates of the effect of resources on convictions. The results are robust to various ways of measuring the number of convictions as well as to various estimators.
Keywords: D72; D73; H83; K42; 330; corruption; rent seeking; enforcement; efficiency wage; public sector wages; system capacity; Korruptionsbekämpfung; Rent-Seeking; Effizienzlohn; Vergütungssystem im öffentlichen Dienst; Teilstaat; USA